Cost and Profit Analysis of Hand Woven Cotton Production : A Case Study Ban Lao Yai, Lao Yai Subdistrict, Kuchinarai District, Kalasin Province - Arsasri, Asst. Prof. Kunteera; Chaiyayong, Kannika; Phosicha, Kunnida (Journal for Developing the Social and Community, 2019)
The objective of this research is to analyze the cost and return of hand-woven cotton products that affect decision making efficiency. Case study of a group of hand-woven cotton manufacturers Big house LAO YAI Kuchinarai District Karasin Province The sample population is (1) women group producing hand-woven cotton, group 1 (2) women group, local weaving group, Moo 7 (3) local fabric weaving group, group 8, these big houses LAO YAI Kuchinarai District Karasin Province.The research instrument is a survey form based on the principles of data analysis in accordance with generally accepted accounting principles and management accounting principles. In the analysis of cost and profit data. The results 1) the women groups made of hand-woven cotton. The costs and profits from the production of hand-woven cotton are as follows : Sales 1,576,900 baht Production costs 734,850 baht Gross profit 842,050 Selling and administrative expenses 31,243 baht Net profit 810,807 baht Net profit margin 51.00% 2) The local weaving group sold 1,404,000 baht, production costs 818,054 baht, gross profit 585,946, selling and administrative expenses 48,200 baht, net profit 537,746 baht, net profit 38.30% 3) Local weaving women group sold 611,950 baht, production cost 523,879 baht, gross profit 88,071, selling and administrative expenses 29,700 baht, net profit 58,371 baht, net profit margin 9.54%